2015
DOI: 10.1177/0308022615599408
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of allotment gardening to health and wellbeing: A systematic review of the literature

Abstract: Introduction: Allotment gardening is a popular pastime which anecdotally contributes to health and wellbeing, although the extent of supportive research evidence is unclear. This systematic review investigates the question: Does allotment gardening contribute to health and wellbeing? Method: A systematic search was conducted, including the terms 'allotment', 'garden', 'health' and 'wellbeing'. Abstracts of identified papers were compared with inclusion criteria, and 10 papers were finally selected. Critical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 21 publications
9
111
0
Order By: Relevance
“…There is increasing awareness among researchers and health practitioners of the potential health benefits derived from gardening activities (Clatworthy et al, 2013, Genter et al, 2015, Wang and MacMillan, 2013). Indeed, previous studies have shown that gardening increases individual's life satisfaction, vigor, psychological wellbeing, positive affects, sense of community, and cognitive function (Gigliotti and Jarrott, 2005, Gonzalez et al, 2010, van den Berg et al, 2010, Wakefield et al, 2007, Wichrowski et al, 2005, Wood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing awareness among researchers and health practitioners of the potential health benefits derived from gardening activities (Clatworthy et al, 2013, Genter et al, 2015, Wang and MacMillan, 2013). Indeed, previous studies have shown that gardening increases individual's life satisfaction, vigor, psychological wellbeing, positive affects, sense of community, and cognitive function (Gigliotti and Jarrott, 2005, Gonzalez et al, 2010, van den Berg et al, 2010, Wakefield et al, 2007, Wichrowski et al, 2005, Wood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, surprisingly, to date no meta-analysis has been conducted to assess the consistency of the positive effects of gardening on health. There have recently been two systematic reviews of studies exploring the association between gardening and health (Genter et al, 2015, Wang and MacMillan, 2013). However, since they presented no quantitative synthesis and only focused on health benefits of allotment gardening (Wang and MacMillan, 2013) and for elderly people (Genter et al, 2015), respectively, more comprehensive and convincing evidence is still wanting.…”
Section: Introductionmentioning
confidence: 99%
“…The increased feeling of connection and belonging to their local community contributed to participants feeling less isolated and more supported. This attribute of community gardening is well documented by other studies . Community gardening is recognised as conferring collective efficacy whereby the benefits extend beyond the gardening experience and the garden setting to positively impact broader aspects of individual and community life .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on the impact of allotment gardening concluded that it has the potential to enhance health and wellbeing through providing five things; a social network, a stress-relieving refuge, a healthier lifestyle, contact with nature and opportunities for personal development (Genter, Roberts, Richardson, & Sheaff, 2015). However, the review highlighted the lack of research in this area, with only ten relevant studies identified.…”
Section: Introductionmentioning
confidence: 99%